A pragmatic logic of transparency: development of a model for a compared study of public policy texts in Latin American countries - Mosquera Sadleir, Carlos Mariano (2017)
This article aims to the logical development of a practical and applicable analysis model of argumentative transparency, specifically for the study of public policies. To this end, we draw upon a “political concept of transparency” which redefines pragmatic logic operations in contexts of trust and cooperation between actors. The model combines a principal-agent framework, non-linear assumptions of production of information, and conversational maxims of use of language. This results in an analysis that is focused on the actors’ capacity and their relation. The model also finds a necessary link between active and passive transparency processes, where the building of trust arising from transparency is directly associated with the reduction of control costs. In addition, this article intends to be an applied model, with visual tools related to transparent decision-making processes, protocols for marking up transparency in texts and, finally, an empirical analysis of transparency in the argument of specific public policies. The combination of multiple frameworks and the deduction of a logical model presents an original work for the study of public policies.